Rzeczywistość to metafora – próba kognitywnej analizy metafor w felietonach Jerzego Urbana - Paroń, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
In this article, an attempt is made to analyse metaphors which appeared in Jerzy Urban’s columns, which were published in a weekly magazine entitled “No”. The present author applied Lakoff and Johnson’s (1980) cognitive theory and used their division of metaphors into three types: orientational, ontological and structural. The observer’s metaphors which are used for construal of reality can present the existing reality. The author examined standard patterns of orientational metaphors: MORE IS HIGHER, FUTURE IS FORWARD, and the ontological metaphor: A CONTAINER. As regards structural metaphors, she referred to the use of source domains: THEATRE, ACTOR, WAR, CHIEF, GAME, SPORT, ANIMAL, DISEASE. In the columns, which present the writer’s subjective outlook, metaphors create the reality reflecting the observer’s opinions and ways of conceiving of the world. They perform a cognitive and persuasive function at the same time. The reader subconsciously starts to behave according to the mechanism of the cognitive theory.